Zero Diffusion-Dispersion-Smoothing Limits for a Scalar Conservation Law with Discontinuous Flux Function - H. Holden; K. H. Karlsen; D. Mitrovic (International Journal of Differential Equations)
We consider multidimensional conservation laws with discontinuous flux, which are regularized with vanishing diffusion and dispersion terms and with smoothing of the flux discontinuities. We use the approach of H-measures to investigate the zero diffusion-dispersion-smoothing limit.